Variation in Criminal Justice Policy-Making: An Exploratory Study Using Sex Offender Registration and Community Notification Laws. (April 2015) - Lytle, Robert
Variation in Sex Offender Registration and Community Notification (SORCN) policies may suggest differences in public fears of sexual crimes as well as differences in state-level policy-making. This study explored the standardization of SORCN policies across a sample of five midwestern states. A thematic content analysis showed that states varied in how registrants were defined, what information was selected for public notification, and how sex offender laws are maintained. A typology of revisions emerged, which may inform our understanding about policy-making. Ultimately, existing research provides limited explanations for these results, serving as an impetus for future research on context and process of criminal justice policy change.